2004
DOI: 10.1182/blood-2004-01-0336
|View full text |Cite
|
Sign up to set email alerts
|

Adult bone marrow-derived cells recruited during angiogenesis comprise precursors for periendothelial vascular mural cells

Abstract: Bone marrow (BM)-derived cells are thought to participate in the growth of blood vessels during postnatal vascular regeneration and tumor growth, a process previously attributed to stem and precursor cells differentiating to endothelial cells. We used multichannel laser scanning confocal microscopy of whole-mounted tissues to study angiogenesis in chimeric mice created by reconstituting C57BL mice with genetically marked syngeneic BM. We show that BM-derived endothelial cells do not significantly contribute to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
238
1
6

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 368 publications
(261 citation statements)
references
References 27 publications
16
238
1
6
Order By: Relevance
“…The involvement of BM-MLCs in physiological revascularization is in agreement with earlier studies that BM-derived cells contribute to the growth of blood vessels during postnatal vascular regeneration and vascular remodeling after injury. 24,25 In the CNS, BM-MLCs and activated microglias can be seen at the border of cerebral infarcted areas in the ischemic brain, 26 as we observed at the border between vascular and avascular retina (Figure 4a). The cells in the cerebral ischemic areas may secrete a variety of proinflammatory cytokines, 27 neurotrophic factors, and angiogenic factors such as VEGF.…”
Section: Discussionmentioning
confidence: 70%
“…The involvement of BM-MLCs in physiological revascularization is in agreement with earlier studies that BM-derived cells contribute to the growth of blood vessels during postnatal vascular regeneration and vascular remodeling after injury. 24,25 In the CNS, BM-MLCs and activated microglias can be seen at the border of cerebral infarcted areas in the ischemic brain, 26 as we observed at the border between vascular and avascular retina (Figure 4a). The cells in the cerebral ischemic areas may secrete a variety of proinflammatory cytokines, 27 neurotrophic factors, and angiogenic factors such as VEGF.…”
Section: Discussionmentioning
confidence: 70%
“…These observations further established the identity of X-gal-positive cells as pericytes, and confirmed that a small fraction of this cell type is generated by cell fusion under normal conditions. Several groups have recently shown the contribution of BMDC and hematopoietic stem cells to the formation of pericytes after stroke (Kokovay et al, 2006;Rajantie et al, 2004). To study the implication of cell fusion during poststroke angiogenesis, a cerebral ischemia/hypoxia episode was induced in 2 months old BMDC chimeric mice.…”
Section: Resultsmentioning
confidence: 99%
“…For instance studies have identified bone marrow-derived PDGFR-β + /Sca-1 + /CD11b + pericyte progenitors [102], bone marrow-derived CD45 + /CD11b + progenitors [103], and Sca-1 + /Tie2 + /CD13 + pericyte progenitors that have been associated with tumour development [104]. To our knowledge, there is no information on the osteochondrogenic capacity of these cells and as such their potential roles during HO remains unknown.…”
Section: Pericyte Progenitor Cellsmentioning
confidence: 99%